Editorial - Vargas, Emgelberth (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2022)
The first issue of the Global Negotium Magazine in this year 2022, corresponding to the months January/April, is aimed at the dissemination of works developed on: Corporate social leadership, managerial strategy, prospective strategic analysis, pedagogical transformational leadership, reconstruction of the social fabric , support networks, communication skills, thoughts of the business world and high-performance teams.